Phylogenomics of Characidae, a hyper-diverse Neotropical freshwater fish lineage, with a phylogenetic classification including four families (Teleostei: Characiformes) - Melo, Bruno F.; Ota, Rafaela P.; Benine, Ricardo C. [UNESP]; Carvalho, Fernando R.; Lima, Flavio C.T.; Mattox, George M.T.; Souza, Camila S. [UNESP]; Faria, Tiago C. [UNESP]; Reia, Lais [UNESP]; Roxo, Fabio F.; Valdez-Moreno, Martha; Near, Thomas J.; et al. (Oxford University Press (OUP), 2024)
Neotropical tetras of the family Characidae form the largest and most taxonomically complex clade within the order Characiformes. Previous phylogenetic relationships concur on the recognition of four major subclades, whereas knowledge on intergeneric and interspecific relationships remains largely incomplete or nonexistent. We sampled 575 specimens of 494 species and 123 genera classified in Characidae, generated new molecular data of ultraconserved elements (UCEs), and used likelihood and Bayesian analyses. The phylogeny (1348 UCE loci: 538 472 bp) yielded clades with unprecedented resolution at species- and genus-levels, allowing us to propose a new classification of former Characidae into four families: Spintherobolidae, Stevardiidae, Characidae, and Acestrorhamphidae. The family Stevardiidae includes nine subfamilies: Landoninae, Xenurobryconinae, Glandulocaudinae, Argopleurinae, Hemibryconinae, Stevardiinae, Planaltininae, Creagrutinae, and Diapominae. The family Characidae includes five subfamilies: Aphyocharacinae, Cheirodontinae, Exodontinae, Tetragonopterinae, and Characinae. The family Acestrorhamphidae congregates 15 subfamilies: Oxybryconinae, Trochilocharacinae, Stygichthyinae, Megalamphodinae, Stichonodontinae, unnamed subfamily, Stethaprioninae, Pristellinae, Jupiabinae, Tyttobryconinae, Hyphessobryconinae, Thayeriinae, Rhoadsiinae, Grundulinae, and Acestrorhamphinae. The phylogeny resolves intergeneric relationships and supports revalidation of Myxiops, Megalamphodus, Ramirezella, Holopristis, and Astyanacinus, synonymy of Aphyodite, Genycharax, and Psellogrammus, and expansion of Cyanogaster, Makunaima, Deuterodon, Hasemania, Hemigrammus, Bario, Ctenobrycon, and Psalidodon. The phylogeny opens avenues for new systematic reviews and redefinitions of included genera.
Keywords: Neotropics; Ostariophysi; phylogeny; tetras; ultraconserved elements